A Model for Visualizing Critical Least Association Rules - Noraziah, Ahmad; Zailani, Abdullah; Herawan, Tutut; Mustafa, Mat Deris (SERSC, 2014)
Mining least association rules has received a great attention from the past decades. However, no current research has been specifically performed for visualizing these types of rules. In this paper, a model for visualizing critical least association rules is presented. The proposed model contains five main steps, including scanning dataset, constructing Least Pattern Tree (LP-Tree), applying Critical Relative Support (CRS), capturing Critical Least Association Rules and finally visualizing the respective rules.